2015
DOI: 10.3109/09638237.2014.998808
|View full text |Cite
|
Sign up to set email alerts
|

The bolstering effect of conceptual priming on psychological help-seeking attitudes in men

Abstract: The findings are the first to suggest that conceptual priming of this kind can be used an as effective and time-efficient intervention by mental health professionals to encourage men to seek help for psychological problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…There was a substantial level of agreement between the two authors (ISO and LB) completing the EPHPP quality assessment (Thomas, 2003; κ = 0.80). Of the nine studies included, three were scored as having “strong” quality (King et al, 2018; Syzdek et al, 2016; Yousaf & Popat, 2015), while five were deemed “moderate” in quality (Hammer & Vogel, 2010; McFall et al., 2000; Pal et al., 2007; Rochlen et al, 2006; Syzdek et al, 2014). One study was scored as having “weak” quality (MacNeil et al, 2018; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was a substantial level of agreement between the two authors (ISO and LB) completing the EPHPP quality assessment (Thomas, 2003; κ = 0.80). Of the nine studies included, three were scored as having “strong” quality (King et al, 2018; Syzdek et al, 2016; Yousaf & Popat, 2015), while five were deemed “moderate” in quality (Hammer & Vogel, 2010; McFall et al., 2000; Pal et al., 2007; Rochlen et al, 2006; Syzdek et al, 2014). One study was scored as having “weak” quality (MacNeil et al, 2018; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Engagement strategies comprised of three interventions delivering a brochure (Hammer & Vogel, 2010; McFall et al., 2000; Rochlen et al, 2006) and one study delivering a three-part video documentary (King et al, 2018) to improve help-seeking. RCTs/pilot RCTs included two RCTs (Pal et al, 2007; Yousaf & Popat, 2015) and two pilot RCTs (Syzdek et al, 2014, 2016). The last intervention was a retrospective review comparing referral rates before and after the instalment of a male-sensitive assessment and treatment program (MacNeil et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may therefore explain why women showed clinical benefits, and men did not. The lack of engagement to mental health treatment in men, is also reflected in the wider literature around help-seeking behaviours, in which men were found to hold more negative attitude towards the utilisation of mental health services when compared to women (Addis and Mahalik, 2003; Mackenzie et al ., 2006; Yousaf and Popat, 2015). A 2019 systematic review on the use of behaviour change techniques for improving mental health utilisation in men, found that ‘problem-solving’ and ‘behaviour change motivation’ were among the key processes identified to improve help-seeking attitudes, behaviours and intentions in men (Sagar-Ouriaghli et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%